SPE/IADC Drilling Conference and Exhibition 2011
DOI: 10.2118/139939-ms
|View full text |Cite
|
Sign up to set email alerts
|

Collapse Prediction Methodology for the Solid Expandable Tubular

Abstract: This paper summarizes an experimental and numerical study aimed at understanding the collapse resistance of expandable tubulars (EXP-T), both before and after expansion, and at constructing a prediction method for post-expanded collapse. Post-expanded collapse resistance is one of the important properties for EXP-T, and the high-collapse EXP-T is necessary for the realization of expandable tubular monobore wells. Thus, a reliable prediction technique can be useful for casing-design utilizing EXP-T. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…From Eqs. (19) and (20), it can be concluded that at time t n + t, every DOF of displacement can meet one autonomous equation, which contains the value of DOF of displacement in time t n and time t n − t, and thus, the matrix factorization is unnecessary.…”
Section: Dynamic Motion Model Of Solid Expandable Tubular During Expamentioning
confidence: 99%
See 1 more Smart Citation
“…From Eqs. (19) and (20), it can be concluded that at time t n + t, every DOF of displacement can meet one autonomous equation, which contains the value of DOF of displacement in time t n and time t n − t, and thus, the matrix factorization is unnecessary.…”
Section: Dynamic Motion Model Of Solid Expandable Tubular During Expamentioning
confidence: 99%
“…Al-Abri [18] conducted a mechanical analysis and load calculation study for an expandable casing based on the elastic-plastic mechanics, but the stress-hardening effect of the casing material in the plastic stage and the impact of curved casing on the axial stress increment within the transition from the expansion section to the sizing section was ignored. Jun et al [19] and Qiang et al [20] aimed at understanding the collapse resistance both before and after expansion of SET by summarizing the experimental and theoretical study.…”
Section: Introductionmentioning
confidence: 99%